Patient at Risk: Emergency medical service providers' opinions on improving an electronic emergency information form database for the medical care of children with special health care needs. Issue 2 (April 2020) - Piibe, Quinn; Kane, Erica; Melzer-Lange, Marlene; Beckmann, Kathleen
Abstract: Background: Patient at Risk (PAR) is an online database using an emergency information form (EIF) that parents of children with special health care needs (CSHCN) complete to store their child's medical information. Emergency medical service (EMS) providers can then access PAR during medical emergencies or for pre-planning. PAR was active for over 10 years but use by patients and EMS was limited. Objective: To determine EMS perspectives on why PAR was not used to its full potential and how to improve PAR for EMS. Methods: Seven questions regarding PAR were developed and presented in focus groups at 32 fire/ambulance houses in southeast and central Wisconsin from June to August 2017. Responses were transcribed and reviewed for themes. Results: 146 EMS providers participated and 11% were aware of PAR. Many did not use PAR because of a lack of follow up or barriers such as limited internet access, inconvenience, other urgent responsibilities, and not knowing when to use PAR. Solutions to these issues include developing or purchasing new technology, involving the dispatch operator in PAR, and returning to a paper-based EIF. The EIF layout and content received very positive reviews with few changes suggested. Most providers felt PAR was important because it would help them provide better care and feel more comfortable treating CSHCN. Conclusion: Despite technological and logistical barriers, EMS providers want online EIF databases for pre-planning and utilization during ambulance runs so they can practice more informed and focused care, especially for vulnerable and medically challenging CSHCN.